Introduction to an Exploration of the Economic and Social Determinants of Mining Accidents in Colombia, 2012–2022 - Bejarano Ibañez, Jazmín Llorena (2025)
Despite the regulations issued by government regulatory bodies, mining emergencies have increased in recent years. This trend may be attributed to the lack of clear identification of the economic and social determinants of mining accidents in Colombia. For this reason, mining accidents during the period 2012–2022 were analyzed in relation to economic and social variables such as: Quarterly Production and Royalties of the mines; the Armed Conflict Incidence Index (IICA); the Gini Index; the Unsatisfied Basic Needs indicator (NBI); the presence of artisanal mining; and the monetary poverty rates in the territories where the mines operate. This information was analyzed using Pearson correlation coefficients and a simple correspondence analysis in R. The results indicate that production levels, the legal status of mining operations, the IICA, and the NBI may be key determinants of mining accidents, particularly when analyzed in the context of the specific mineral being extracted.